COMBINED REDUCED FORCED EXPIRATORY VOLUME IN 1-SECOND (FEV1) AND PERIPHERAL ARTERY DISEASE IN SEDENTARY ELDERS WITH FUNCTIONAL LIMITATIONS - Vaz Fragoso, Carlos A. (2014)
OBJECTIVES: Because they are potentially modifiable and may coexist, we evaluated the combined occurrence of a reduced forced expiratory volume in 1-second (FEV1) and peripheral artery disease (PAD), including its association with exertional symptoms, physical inactivity, and impaired mobility, in sedentary elders with functional limitations. DESIGN: Cross-sectional. SETTING: Lifestyle Interventions and Independence in Elder (LIFE) Study. PARTICIPANTS: 1307 sedentary community-dwelling persons, mean age 78.9, with functional limitations (Short Physical Performance Battery [SPPB] <10). MEASUREMENTS: A reduced FEV1 was defined by a Z-score <-1.64 (< lower limit of normal), while PAD was defined by an ankle-brachial index <1.00. Exertional dyspnea was defined as moderate-to-severe (modified Borg index), immediately after a 400-meter walk test (400MWT). Exertional leg symptoms were established by the San Diego Claudication Questionnaire. Physical inactivity was evaluated by percent of accelerometry wear-time with activity <100 counts/min (top quartile established high sedentary-time). Mobility was evaluated by the 400MWT (gait-speed <0.8 m/s defined as slow) and SPPB (≤7 defined moderate-to-severe mobility impairment). RESULTS: A combined reduced FEV1 and PAD was established in 6.0% (78/1307) of participants. However, among those who had a reduced FEV1, 34.2% (78/228) also had PAD, while 20.8% (78/375) of those who had PAD also had a reduced FEV1. The two combined conditions were associated with exertional dyspnea (adjusted odds ratio [adjOR] 2.59 [1.20, 5.60]) and slow gait-speed (adjOR 3.15 [1.72, 5.75]) but not with exertional leg symptoms, high sedentary-time, and moderate-to-severe mobility impairment. CONCLUSIONS: In sedentary community-dwelling elders with functional limitations, a reduced FEV1 and PAD frequently coexisted and, in combination, were strongly associated with exertional dyspnea and slow gait-speed (a frailty indicator that increases the risk of deleterious outcomes).